The FtsH-Inactive Protein FtsHi5 Is Required for Chloroplast Development and Protein Accumulation in Chloroplasts at Low Ambient Temperature in Arabidopsis - Li, Jin-Yu; Sun, Jing-Liang; Tian, Ying-Ying; Liu, Jian-Xiang (Frontiers in Plant Science, 2022)
Chloroplasts are indispensable for higher plants. The growth and development of plants are very sensitive to environmental temperature changes, and chloroplast development is also regulated by adverse environmental temperatures. However, the molecular mechanism of how plants coordinate chloroplast development and environmental temperature changes remains largely unknown. Here, a temperature-conditioned chloroplast development defective mutant thermo-sensitive mutant in leaf color 2 (tsl2) of Arabidopsis was obtained through a forward genetic screening. The tsl2 mutant showed a weak yellowish phenotype at normal growth temperature (22°C), and the phenotype was more pronounced at low growth temperature (16°C) and largely rescued at high growth temperature (29°C). Bulk Segregant Analysis (BSA) revealed that TSL2 encodes FtsH-Inactive Protein 5 (FtsHi5). Genetic complementation analysis confirmed that complemented expression of FtsHi5 rescued the chlorophyll content and thylakoid development defects observed in tsl2 mutants at 16°C. Quantitative mass spectrometry analysis with Tandem Mass Tag (TMT) isobaric labeling revealed broad changes in the chloroplast proteome of tsl2 mutant plants at low temperature, which is agreed with the impaired chloroplast biogenesis and function in tsl2 plants. Together, our data demonstrates that FtsHi5/TSL2 plays an important role in chloroplast development and protein accumulation in chloroplasts, especially at low environmental temperatures in Arabidopsis.